Evaluation of Effects and Effectiveness of Various α and β Angulations for Three Different Loop Made of Stainless Steel Arch Wires – A FEM Study - Supradeep Kumar Kamisetty (Journal of Clinical and Diagnostic Research, 2014)
Introduction: Evaluations on retraction loop designs have been limited to describe the force systems applied to the buccal surfaces of the tooth that can be in different planes resulting undesirable effects, needing corrective action in future. By initially understanding these effects, modifications to the loop design can essentially counteract the undesired affects. Aim: To deter-mine Moments & M/F ratios produced by different gabling in the three retraction loops (Tear drop loop, T-loop, Open vertical loop) and movement of the anterior teeth and posterior teeth) of the maxillary arch in an extraction model, on activation of three retraction loops by1 mm. Materials and Methods: A PC with Quad core processor, 8GB RAM, 1TB storage space and Graphic Accelerator was used. Computer Software: ANSYS Version11, PRO/ENGINEER was used in the study. The first step is modeling, done by using Pro/ Engineer software and for creating a model the CT scan data is required. The maxilla with teeth of a patient is scanned at various sections at regular intervals of 0.5 mm. These scanned images are then imported into Pro/E software to various offset planes. Once imported, the software can do an automatic meshing and establishes contact automatically. Results: When angulations increases intrusive or extrusive movements and movements in horizontal direction of crown tip and root tip increases. All values of T-loop are more than Teardrop loop and less than Open vertical loop. Conclusion: FEM study concludes that Teardrop loop with 10- 20(α-β) combination is preferred for Group A anchorage.